Beta-carotene in the prevention of photodegradation of multivitamin preparations - Comia, Amor L.; Quirino, Joselito (Manila Department of Pharmaceutical Chemistry, College of Pharmacy, University of the Philippines, 1994)
In this study, beta-carotene, a provitamin A, is used to hinder the photodegradation of two photolabile vitamin, thiamin and alpha-tocopherol. Assays were performed using spectrophotometric analysis for vitamin E and flourimetry for thiamin to be able to detect the presence of degradation products. Although beta-carotene can contribute to a certain degree to the stability of the vitamins, it has been proven that the use of the amber bottle is still the best way to protect thiamin and alpha-tocopherol against photodegradation.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, March 1994.
Keywords: Beta carotene; Vitamins